Effect of boron powder purity on superconducting properties of MgB2 - Xu, Xun; Qin, M. J.; Konstantinov, K.; dos Santos, Dayse I.; Yeoh, W. K.; Kim, J. H.; Dou, S. X. (Iop Publishing Ltd, 2006)
The effect of the properties of starting boron powders on the superconducting properties of MgB2 has been studied. The 92% and 96% pure powders produce lower surface reactivity and larger particle size than the 99% boron powder, as can be seen from Brunauer - Emmett - Teller (BET) and scanning electron microscopy (SEM) results, indicating that the low purity powders cannot be used to archive the same superconducting properties as those of samples made from pure 99% boron powder. However, the purity of 92% and 96% boron powders can be improved by using a simple chemical process, leading to enhanced magnetic critical current densities J(c). From x-ray diffraction (XRD) measurement, oxide impurity has been observed, which might be originated from the B2O3 phase in the boron powders. In order to get high performance MgB2, it is obviously important to control the phase composition and microstructure of amorphous boron starting powders and solid reaction conditions.